STUDY OF AMINOACID COMPOSITION OF THE HARICOT BEAN SHELLS - Kriukova І.; Gubar, S.; Vladymyrova, I.; Tishakova, T. (Scientific Journal of Pedagogy and Economics, 2020)
Commonly, the production of herbal medicines is more advantageous economically than chemical synthesis. Agricultural crops, having sufficient raw material base, are of main interest. In this respect the shells of haricot bean (Phaseolus vulgaris L. (Fabaceae)), that are waste products of beans, are of special interest. Due to the absence of regulatory documents for this kind of drug raw material in Ukraine the development of standardization parameters for the raw material of haricot bean is a very topical. Pharmacotherapeutic action of this drug raw material is caused by the presence of amino acids, proteins, macro- and microelements as well as flavonoids. There are medicines at the pharmaceutical market of Ukraine that was produced from the haricot bean: «Sadifit» (ZAO «Liktravy», Ukraine), «Arphazetin» (ZAO Pharmaceutical plant «Viola», Ukraine), «Hepatophyt» (LLC «Research and production pharmaceutical company «AIM», Ukraine), «Shells of haricot bean» (ZAO «Liktravy», Ukraine). Medicines are introduced to the market in the form of medicinal herbs mixture that’s why main method of application is a preparation of restorative drinks, tinctures, teas. In light of this, study of amino acid composition in the water extracts from raw material is reasonable. Research of qualitative and quantitative amino acid composition of 5 lots of the shells of haricot bean was carried out by HPLC method. This raw material was harvested in different regions of Ukraine over a period of 2014 – 2016. 16 amino acids were identified in the water extracts of the shells of haricot bean. Glutamic acid (1.60 – 5.56 ´μg/100 mg), L-alanine (1.41 – 2.23 μg/100 mg), L-arginine (0.65 – 2.12 μg/100 mg) had the greatest content in the investigated samples. D-serine (0.04 – 0.13μg/100 mg) and D,L-methionine (0.02 – 0.43 μg/100 mg) had the lowest quantity in the investigated samples. Sufficiently high content of amino acids makes it possible to consider them as potential substances-markers at the development of assay procedure for the standardization of raw material.